2018
DOI: 10.1155/2018/4504287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Complications, Their Risk Factors, and the Cardiovascular Risk Factors among Patients with Type 2 Diabetes Attending the Diabetic Clinic at a Tertiary Care Hospital in Sri Lanka

Abstract: Diabetes incurs heavy burden to patients and the healthcare system. Assessment of disease burden is important in taking necessary precautions and management decisions. We aimed to determine the prevalence of macro- and microvascular complications, their risk factors, and coronary artery disease (CAD) risk factors among patients with type 2 diabetes mellitus (T2DM). A descriptive cross-sectional single-centre study was carried out among 3000 patients with T2DM attending the diabetic clinic at the National Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 45 publications
6
45
6
Order By: Relevance
“…33 Another study also reported that age, disease duration, and HBA1c level were related to microvascular complications of diabetes, while only age was related to macrovascular complication of diabetes, which is in line with our findings as we found that only mortality and retinopathy were associated with higher levels of HbA1C. 34 In our study, females without complication had 12% less risk of mortality than males which could be explained by a longer life expectancy in women than men. 35 In females without complication and with CAD, the risk of mortality was lower than males.…”
Section: Discussionsupporting
confidence: 91%
“…33 Another study also reported that age, disease duration, and HBA1c level were related to microvascular complications of diabetes, while only age was related to macrovascular complication of diabetes, which is in line with our findings as we found that only mortality and retinopathy were associated with higher levels of HbA1C. 34 In our study, females without complication had 12% less risk of mortality than males which could be explained by a longer life expectancy in women than men. 35 In females without complication and with CAD, the risk of mortality was lower than males.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained after a 24-month follow-up period demonstrated that 93 (54.1%) patients required LEA, with 80 (46.5%) requiring minor amputation and 13 (7.6%) requiring major amputation. The rate of major LEA in this study was considerably lower than the corresponding rate observed in some previous trials [43][44][45]. Furthermore, during the 24-month follow-up period, the risk of LEA was highly associated with newly developed ischemic heart disease, with 49.5% (n = 46) of the patients who underwent LEA developing this disease as compared with 32.9% (n = 26) of the patients who did not undergo LEA (P = 0.028).…”
Section: Discussioncontrasting
confidence: 86%
“…Hyperglycaemia and hyperlipidaemia are known risk factors for vascular complications [10,11,14]. However, these associations were not significant in this study.…”
Section: Plos Onecontrasting
confidence: 61%
“…This study aimed to determine the prevalence of vascular complications among these patients and factors independently associated with vascular complications. Similar studies have been conducted in other populations and settings [10][11][12][13][14][15][16][17]. However, the evidence in this particular population and setting could be different from others, and this needs exploration and reporting.…”
Section: Introductionmentioning
confidence: 72%